Detection of Babesia odocoilei in Ixodes scapularis Ticks Collected in Southern Ontario, Canada - John D. Scott; Emily L. Pascoe; Muhammad S. Sajid; Janet E. Foley (Pathogens, 2021)
Tick-borne zoonotic diseases have an economic and societal impact on the well-being of people worldwide. In the present study, a high frequency of Babesia odocoilei, a red blood cell parasite, was observed in the Huronia area of Ontario, Canada. Notably, 71% (15/21) blacklegged ticks, Ixodes scapularis, collected from canine and feline hosts were infected with B. odocoilei. Consistent with U.S. studies, 12.5% (4/32) of questing I. scapularis adults collected by flagging in various parts of southwestern Ontario were positive for B. odocoilei. Our data show that all B. odocoilei strains in the present study have consistent genetic identity, and match type strains in the GenBank database. The high incidence of B. odocoilei in the Huronia area indicates that this babesial infection is established, and is cycling enzootically in the natural environment. Our data confirm that B. odocoilei has wide distribution in southern Ontario.